Clinical and Economic Impact of Implementing OVIVA Criteria on Patients With Bone and Joint Infections in Outpatient Parenteral Antimicrobial Therapy. (11th October 2019) - Marks, Michael; Bell, Lucy C K; Jones, Imogen; Rampling, Tommy; Kranzer, Katharina; Morris-Jones, Stephen; Logan, Sarah; Pollara, Gabriele
Abstract: The OVIVA study demonstrated noninferiority for managing bone and joint infections (BJIs) with oral antibiotics. We report that 79.7% of OPAT patients being treated for BJIs at our center would be eligible for oral antibiotics, saving a median (IQR) 19.5 IV-antibiotic days (8.5–37) and GBP 1234 (569–2594) per patient.